We Will Be Heard: Women's Struggles for Political Power in the United States - Freeman, Jo (Rowman & Littlefield Publishers, 2008)
In We Will Be Heard, noted political scientist Jo Freeman chronicles the struggles of women in the United States for political power. Most of their stories are little-known, but Freeman's compelling portrait of women working for change reminds us that women have never been silent in the political affairs of the nation. From J. Ellen Foster's address to the 1892 Republican Convention to Nancy Pelosi's 2007 election as the first female Speaker of the House, women have worked to influence politics at every level. Well before most could vote, women campaigned for candidates and lobbied to shape public policy. Men welcomed their work, but not their ideas. Even with equal suffrage women faced many barriers to full political participation. The fifteen case studies of women's struggles for political influence in this book provide the historical context for today's political events. Starting with an overview of when and why political women have been studied, the three sections of the book look at different ways in which women have broken barriers, practiced politics, and promoted public policy. These engaging and accessible stories are even more important in today's political climate, when a woman can finally be a front-runner in a presidential race. Readers of all political stripes will enjoy the history behind modern politics in this story of women struggling to make their voices heard.